Expanding Cervical Cancer Screening and Treatment in Tanzania: Stakeholders' Perceptions of Structural Influences on Scale‐Up. (29th April 2015) - McCree, Renicha; Giattas, Mary Rose; Sahasrabuddhe, Vikrant V.; Jolly, Pauline E.; Martin, Michelle Y.; Usdan, Stuart Lawrence; Kohler, Connie; Lisovicz, Nedra
Abstract : Tanzania has the highest burden of cervical cancer in East Africa. This study aims to identify perceived barriers and facilitators that influence scale‐up of regional and population‐level cervical cancer screening and treatment programs in Tanzania. Convenience sampling was used to select participants for this qualitative study among 35 key informants. Twenty‐eight stakeholders from public‐sector health facilities, academia, government, and nongovernmental organizations completed in‐depth interviews, and a seven‐member municipal health management team participated in a focus group discussion. The investigation identified themes related to the infrastructure of health services for cervical cancer prevention, service delivery, political will, and sociocultural influences on screening and treatment. Decentralizing service delivery, improving access to screening and treatment, increasing the number of trained health workers, and garnering political will were perceived as key facilitators for enhancing and initiating screening and treatment services. In conclusion, participants perceived that system‐level structural factors should be addressed to expand regional and population‐level service delivery of screening and treatment. Implications for Practice: Tanzanian women have a high burden of cervical cancer. Understanding the perceived structural factors that may influence screening coverage for cervical cancer and availability of treatment may be beneficial for program scale‐up. This study showed that multiple factors contribute to the challenge of cervical cancer screening and treatment in Tanzania. In addition, it highlighted systematic developments aimed at expanding services. This study is important because the themes that emerged from the results may help inform programs that plan to improve screening and treatment in Tanzania and potentially in other areas with high burdens of cervical cancer. Abstract : This qualitative study showed that multiple factors contribute to the challenge of cervical cancer screening and treatment in Tanzania and highlighted systematic developments aimed at expanding services. The themes that emerged from the results may help inform programs that plan to improve screening and treatment in Tanzania and potentially in other areas with high burdens of cervical cancer.